Pengelolaan Taman Bacaan Masyarakat dalam Kemajuan Literasi pada Pondok Maos Guyub Kendal - Indriyani, Isti; Raharjo, Tri Joko; Ilyas, Ilyas (Universitas Negeri Semarang, 2017)
The purpose of this research is Described: (1) management of TBM Pondok Maos Guyub, and (2) the impact of the TBM Pondok Maos Guyub Progress Towards Literacy community. This research uses qualitative approach method. The subject is the founder of TBM, TBM visitor Manager and several surrounding communities TBM. Engineering data collection done by observation, interviews, and documentation. Data analysis techniques include the collection of data, data presentation, data reduction and withdrawal of the conclusion. An examination of the validity of the data using triangulation of sources. The research results showed that: (1) process management of TBM Pondok Maos Guyub includes the planning, organizing, implementasion, coaching, assessment and development. (2) the impact of the management of TBM against perceived community literacy progress impact on academic skills, personal skills, and competence of the Polytechnic.